Investigating the profit efficiency of garri processors at the post-harvest value chain in Rivers State, Nigeria - Nwahia, Ogechi; Mulikat Kehinde, Elemasho; Nwebor, Emmanuel; Egwuma, Henry; Chukwuemeka, Aneke Chigozie; Icha, Eke Stephen (Talenta Publisher, 2025)
The study focused on the profit efficiency of garri processors at the post-harvest value chain in Rivers State, Nigeria. A purposive sampling procedure and snowballing techniques were used to select 120 respondents for this study. The study utilized primary data collected with the aid of a structured questionnaire and analyzed using descriptive statistics and inferential statistics, such as the Stochastic (profit function) frontier model. The results revealed that more than 75% of the garri processors in Rivers State were female. The results revealed that garri processors were 37% profit-efficient, while the cost of cassava roots, the cost of grating/milling, the cost of hiring equipment, and the cost of transportation were negatively affecting the profit of garri processors. Years of experience in garri processing and education decrease the profit inefficiency of garri processors, while the cost of the cassava roots increases the profit inefficiency of the garri processors in Rivers State. The study suggested that adequate training should be conducted for garri processors in Rivers State by the extension agents and the Nigeria Stored Products Research Institute (NSPRI), and the government should provide incentives for such training. Also, garri processors in Rivers State should be encouraged to adopt the garri processing plant installed by the Rivers State government.